Effect of pistachio consumption on the modulation of urinary gut microbiota-related metabolites in prediabetic subjects - Hernández-Alonso, Pablo; Cañueto, Daniel; Giardina, Simona; Salas-Salvadó, Jordi; Cañellas, Nicolau; Correig, Xavier; Bulló, Mònica (The Journal of nutritional biochemistry, 2017)
The specific nutritional composition of nuts could affect different metabolic pathways involved in a broad range of metabolic diseases. We therefore investigated whether chronic consumption of pistachio nuts modifies the urine metabolome in prediabetic subjects. We designed a randomized crossover clinical trial in 39 prediabetic subjects. They consumed a pistachio-supplemented diet (PD, 50% carbohydrates, 33% fat, including 57 g/d of pistachios daily) and a control diet (CD, 55% carbohydrates, 30% fat) for 4 months each, separated by a 2-week wash-out. Nuclear magnetic resonance (NRM) was performed to determine changes in 24-h urine metabolites. Significant changes in urine metabolites according to the different intervention periods were found in uni- and multivariate analysis. Score plot of the first two components of the multilevel partial least squares discriminant analysis (ML-PLS-DA) showed a clear separation of the intervention periods. Three metabolites related with gut microbiota metabolism (i.e., hippurate, p-cresol sulfate and dimethylamine) were found decreased in PD compared with CD (P<.05). Moreover, cis-aconitate [intermediate of the tricarboxylic acid (TCA)] was also found decreased following PD compared with CD. Intragroup analysis showed that creatinine levels were significantly increased in PD (P=.023), whereas trimethylamine N-oxide (TMAO) was found significantly reduced following PD (P=.034). Our results suggest that chronic pistachio consumption may modulate some urinary metabolites related to gut microbiota metabolism and the TCA cycle; all associated with metabolic derangements associated with insulin resistance and Type 2 diabetes.